The Effect of STEM-Based Mathematics and Natural Science Teaching Materials on Students' Critical and Creative Thinking Skills: A Meta-Analysis - Aprina Maharani Zan; Korry Nilyani; Riza Azriyanti; Asrizal Asrizal; Festiyed Festiyed (Postgraduate, University of Mataram, 2023)
Students must possess 21st century abilities, including the ability to think critically and creatively, in order for education to be developed for this century. Teaching materials are required to support students' learning as they develop these skills. The development of the 21st century cannot be separated from technological developments which are developing rapidly so that Science, Technology, Engineering and Mathematics (STEM) based teaching materials are very popular to use. The goal of the study was to ascertain how STEM-based instructional materials affected students' capacity for critical and creative thought. The research method used is meta-analysis of 22 national and international journal articles. The research results obtained are with variations in the level of educational units, teaching material subjects, critical and creative thinking skills as well as the variety of teaching materials used state that the use of STEM-based teaching materials has a significant influence on students' critical and creative thinking skills. The conclusion from this meta-analysis research is that there is a significant influence from the use of STEM-based teaching materials on students' critical and creative thinking skills